2002
DOI: 10.1136/jcp.55.8.602
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase activity detected in oral lichen planus by RNA in situ hybridisation: not a marker for malignant transformation

Abstract: Background: Oral lichen planus (OLP) is a chronic inflammatory condition. Clinically, it is characterised by the presence of a white lace-like lesion on the buccal mucosa, tongue, and gingivae, with erosions and ulceration. The World Health Organisation considers OLP to be a premalignant condition. Aims: To investigate expression of the telomerase RNA component (hTR) in OLP compared with normal control buccal mucosa and to assess the possibility of using hTR expression as a marker for malignant transformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Although both CP and OLP are inflammatory diseases, it has been suggested that patients with OLP have a higher risk for developing OSCC based on clinical studies and case reports 38‐40 . However, research on several surrogate endpoints such as telomerase activity, P53, loss of heterozygosity, and cytogenetic abnormality did not show convincing or consistent evidence of premalignant potential as those found in epithelial dysplasia 41‐46 . Therefore, whether OLP is premalignant remains an unclear and controversial issue 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Although both CP and OLP are inflammatory diseases, it has been suggested that patients with OLP have a higher risk for developing OSCC based on clinical studies and case reports 38‐40 . However, research on several surrogate endpoints such as telomerase activity, P53, loss of heterozygosity, and cytogenetic abnormality did not show convincing or consistent evidence of premalignant potential as those found in epithelial dysplasia 41‐46 . Therefore, whether OLP is premalignant remains an unclear and controversial issue 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Much of this work has focused on the T cells that invade the stroma. Primers were designed for q-RT-PCR analysis of CD14 18 , TLR1, TLR2, TLR6 19 , IL10 20 , HIF1 27 , hTR 28 , and TRPV1 29 . RNA for IL6 and IL8, two proteins that have been shown in multiple reports to be increased with OLP and to be synthesized by keratinocytes were also examined.…”
Section: Methodsmentioning
confidence: 99%
“…To uncover some of the molecular genetic aberrations associated with OLP, investigators have used molecular and genetic methods such as loss of heterozygosity (LOH) (Zhang et al, 2000), chromosome in situ hybridization (Kim et al, 2001), p53 and c-erbB2 expression (Girod et al, 1994(Girod et al, , 1995Kilpi et al, 1996;Ogmundsdottir et al, 2002), and telomerase activity (O'Flatharta et al, 2002). However, none of these methods appears to provide definitive predictive information with regard to the malignant potential of a lesion diagnosed as OLP.…”
Section: Chromosomal Numerical Aberrations In Oral Lichen Planusmentioning
confidence: 98%